Challenges in the Diagnosis and Management of Anterior Blepharitis - Bitton, Etty (Canadian Eye Care Today, 2024)
Blepharitis is defined as inflammation of the eyelids, classified according to anatomical location: anterior (eyelid skin, base of the lashes including the eyelash follicle) or posterior (meibomian glands) blepharitis. Although blepharitis is one of the most common ocular disorders, epidemiological data on the condition is lacking, making prevalence difficult to assess. A 2009 survey of eyecare practitioners reported observing blepharitis in 37%–47% of patients in their clinical practice. This observation may vary depending on the age, sex, and types of patients (i.e., dry eye) in the practice. Younger females are found to have more acute short-term presentation of blepharitis, whereas older, more fair-skinned females present with chronic blepharitis often concurrent with rosacea. Large population‑based studies, using a standardized definition and diagnostic technique, are needed to properly assess the prevalence and incidence of blepharitis and to allow for study comparisons among various age groups. The ocular surface, including the lid margin, has a natural flora or microbiome, which is imperative in maintaining the health and defence mechanism of the ocular surface. This can be affected by age, gender, inflammation, disease, medication, cosmetics, and treatment (systemic or topical). An overgrowth of microbes or an imbalance of the natural flora may result in an inflammatory response, leading to blepharitis, conjunctivitis, keratitis, or a combination of these.